The Effect of Progressive Test Implementation on the Cumulative Grade Point Average (GPA) of Medical Students at FKKGIK, Universitas Prima Indonesia in 2024 - Marshall Jeremia Nadapdap; Stevensen Eka Wijaya; Suandy (South Sulawesi Education Development (SSED), 2025)
Progressive Tests are structured, longitudinal formative assessments used globally to evaluate knowledge retention and cognitive development in medical education. While they are increasingly integrated into curricula, limited empirical data exists regarding their predictive validity within Indonesian private medical institutions. Evaluating their impact on academic performance is essential to refine assessment strategies and promote effective learning. This study investigates the influence of Progressive Test scores on the academic performance of medical students at the Faculty of Medicine, Dentistry, and Health Sciences (FKKGIK), Universitas Prima Indonesia during the 2024 academic year. A quantitative, cross-sectional study was conducted using academic records from 160 randomly selected preclinical students. Progressive Test scores were used as the independent variable, while Cumulative Grade Point Average (CGPA) represented the dependent variable. Pearson’s correlation analysis was conducted using SPSS version 27, with a significance level of p < 0.05. The average Progressive Test score was 40.58 (SD ±10.2), and the mean CGPA was 3.30 (SD ±0.28). A strong, positive, and statistically significant correlation was found between Progressive Test scores and CGPA (r = 0.757, R² = 0.573, p < 0.001). These findings indicate that Progressive Test performance significantly predicts academic achievement, explaining 57.3% of the variance in CGPA. Progressive Tests demonstrate strong predictive value for student performance and serve as an effective tool for curriculum monitoring and early academic intervention. Institutionalizing their use in Indonesian medical schools is recommended. Future multicenter and longitudinal studies are suggested to broaden applicability and assess additional influencing factors.